2009
DOI: 10.1093/treephys/tpp112
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor studies of leaf lamina hydraulic conductance in trembling aspen (Populus tremuloides Michx.) leaves

Abstract: The present study investigated leaf water transport properties in trembling aspen (Populus tremuloides) leaves. Leaf lamina hydraulic conductance (K(lam)) and stomatal conductance (g(s)) were drastically suppressed by NaF (a general metabolic inhibitor). In leaves treated with 0.2 mM HgCl(2) (an aquaporin blocker), K(lam) declined by 22% when the leaves were sampled in June but the decline was not significant when the leaves were sampled in August. The leaves sampled in June that transpired 30 mM beta-mercapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…This has indicated no change in apoplastic flow in response to light (see below) in Quercus macrocarpa or Populus tremuloides (Voicu et al, 2009;Voicu and Zwiazek, 2010), while in grapevine a greater degree of apoplastic flow was observed with drought treatment that corresponded to reduced K leaf and reduced inhibition of K leaf by mercury (Pou et al, 2013). Switching of water pathways involving apoplastic and symplastic transport may allow for some flexibility in responses to water stress (Morillon and Chrispeels, 2001).…”
Section: Role Of Aquaporins In Shoot Water Transport Assessing the Romentioning
confidence: 99%
See 1 more Smart Citation
“…This has indicated no change in apoplastic flow in response to light (see below) in Quercus macrocarpa or Populus tremuloides (Voicu et al, 2009;Voicu and Zwiazek, 2010), while in grapevine a greater degree of apoplastic flow was observed with drought treatment that corresponded to reduced K leaf and reduced inhibition of K leaf by mercury (Pou et al, 2013). Switching of water pathways involving apoplastic and symplastic transport may allow for some flexibility in responses to water stress (Morillon and Chrispeels, 2001).…”
Section: Role Of Aquaporins In Shoot Water Transport Assessing the Romentioning
confidence: 99%
“…Feeding aquaporin inhibitors via the cut petiole yields varying results depending on species or even cultivars (Pou et al, 2013), diurnal timing (Postaire et al, 2010), plus or minus light (Voicu and Zwiazek, 2010), circadian oscillations (Nardini et al, 2005), season (Voicu and Zwiazek, 2010), or water stress and recovery cycles (Pou et al, 2013). For grapevine, a variety of aquaporin inhibitors were examined, with mercury giving the most consistent response for two cultivars (cv Shiraz and Chardonnay), though H 2 O 2 was also effective for cv Shiraz.…”
Section: Role Of Aquaporins In Shoot Water Transport Assessing the Romentioning
confidence: 99%
“…During the season, K leaf typically declines during senescence resulting in the loss of photosynthetic capacity (Brodribb and Holbrook 2003a). In some plant species, K leaf has been shown to be sensitive to irradiance (Sack et al 2002(Sack et al , 2003Scoffoni et al 2008;Tyree et al 2005;Voicu et al 2008;Voicu and Zwiazek 2010). However, the processes contributing to this response are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There should be an optimal light intensity to maximize water flow across leaf cells, but enhanced water flow could be inhibited at a certain light intensity. Although recent findings showed an inhibition of aquaporin-mediated water transport in tobacco and bur oak leaves exposed to high irradiance (Lee et al, 2009;Voicu et al, 2009), these papers rather indicate that regulation of the aquaporin-mediated water transport processes is more complicated and can not always be explained merely by changes in the transcript level. On the other hand, it has also been shown that exposure of Arabidopsis plants to darkness increased the hydraulic conductivity of excised rosettes (K ros ) by up to 90% and enhanced the transcript abundance of several PIP genes, including AtPIP1;2 which represent a key component of whole-plant hydraulics (Postaire et al, 2010).…”
Section: Effect Of Light Intensity On Hydraulic Conductivitymentioning
confidence: 88%
“…In many plant species it has been reported that the K leaf , can be increased several folds by high irradiance (Nardini et al, , 2010Lo Gullo et al, 2005;Sack & Holbrook, 2006;Cochard et al, 2007) and can depend on both light duration and intensity (Sellin et al, 2008). Other experiments showed no effect of light conditions on K leaf as it occurs in laurel in laboratory experiments (Laurus nobilis) (Cochard et al, 2004) or on K lam (leaf lamina hydraulic conductance) of trembling aspen trees (Voicu et al, 2009). Despite of it, there is current agreement that aquaporin activation and/or expression plays a role in the underlying mechanisms as the increase in K leaf Voicu et al, 2008).…”
Section: Effect Of Light Intensity On Hydraulic Conductivitymentioning
confidence: 97%